Pengaruh Kompetensi SDM, Sarana Prasarana, dan Metode Pembelajaran terhadap Kepuasan Peserta Didik melalui Kualitas Alumni sebagai Variabel Intervening - Anistya Meinar Rosidah; M Thamrin; Abadi Sanosra (Institut Teknologi dan Sains Mandala, 2025)
The Teaching Hospital is a hospital that aims to provide integrated health, education and research services in the fields of medical and/or dental education, continuing education and other health education in a multi-professional manner. Teaching hospitals are required to be able to encourage student satisfaction. The aim of this research is to analyze the influence of human resource competence, facilities and infrastructure, and learning methods on the quality of alumni and student satisfaction. This research uses a quantitative approach and is summarized as explanatory research. The population in this study was 300 Co-Ass Doctors at dr. Soebandi Hospital. The research sample referred to the Slovin Formula as many as 171 respondents. Data analysis uses Structural Equation Model (SEM) then supported with the help of Smart Partial Least Square (PLS) software. The research results show that human resource competencies and learning methods have a positive effect on student satisfaction. Facilities and infrastructure do not effect on student satisfaction. Human resource competency and learning methods have a positive effect on the quality of alumni. Facilities and infrastructure do effect on the quality of alumni. Student satisfaction has a positive effect on the quality of alumni. Human resource competency and facilities and infrastructure, and learning methods has a positive effect on on student satisfaction through Alumni Quality as an intervening variable. Learning methods do not effect on student satisfaction through Alumni Quality as an intervening variable.